Stand on the shoulders of academia: The effect of academic directors on science-based breakthrough innovations - Li, Yajing; Xia, Jun (Research Policy, 2026)
Drawing on the resource provision perspective within resource dependence theory, we argue that academic directors significantly enhance firms' capacity for science-based breakthrough innovations. This study also engages with a central debate in innovation research: whether external resources and internal capabilities function as complements or substitutes. Using panel data from 991 U.S. publicly listed innovative firms, we find that the presence of academic directors is positively associated with science-based breakthrough innovation, particularly in firms with a strong publication record. This supports the complementary relationship between external scientific expertise and internal R&D capabilities. Robustness checks—including instrumental variable analysis and natural experiments involving the sudden deaths of academic directors—reinforce our findings. These results offer new insights into how strategic leadership can leverage external academic expertise to drive transformative innovation.